2016
DOI: 10.1007/s10661-016-5576-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of monocyclic aromatic hydrocarbons (BTEX) and the impact on macrobenthic community structure in Lagos lagoon, Nigeria

Abstract: The widespread distribution of petroleum products arising from the rapid growth of the petroleum industry in Nigeria has resulted in the pollution of the environment through oil spills involving leakages from tankers, pipelines, tank farms, and dumping of waste petroleum products. The impacts and distribution of major toxic components (benzene, toluene, ethylbenzene, and xylene (BTEX)) of petroleum products in water and sediment samples collected from sampling stations in the Lagos lagoon was investigated over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…All these increase the concentration of these compounds in municipal waters, hence may explain the reason for the higher BTEX content in water over sediment. Doherty and Otitoloju [27] also reported higher total BTEX content in water in comparison with sediment from the Lagos lagoon. According to Fayemiwo [28], the occurrence of BTEX compounds in water is an alarming trend, especially in vulnerable parts of the world such as South-East Asia and Africa where these water bodies are directly relied upon for drinking and other potable uses.…”
Section: Discussionmentioning
confidence: 92%
“…All these increase the concentration of these compounds in municipal waters, hence may explain the reason for the higher BTEX content in water over sediment. Doherty and Otitoloju [27] also reported higher total BTEX content in water in comparison with sediment from the Lagos lagoon. According to Fayemiwo [28], the occurrence of BTEX compounds in water is an alarming trend, especially in vulnerable parts of the world such as South-East Asia and Africa where these water bodies are directly relied upon for drinking and other potable uses.…”
Section: Discussionmentioning
confidence: 92%
“…The vegetation surrounding Lekki Lagoon is of the swampy mangrove type, predominated by Rhizophora racemosa and Avicenia nitida. Bioaccumulation of petrogenic pollutants have previously been reported at this location (Doherty et al, 2010;Doherty and Otitoloju, 2016;Akinsanya et al, 2018).…”
Section: Description Of the Study Areamentioning
confidence: 62%
“…Ammonia aotena was found to be the dominant taxon along the highly polluted area north of Lagos Harbor (ST4), a finding that is concordance with the presence of living individuals from this area [7,8]. The area is impacted by highest concentrations of both carcinogenic polycyclic aromatic hydrocarbons (PAH), heavy metal pollutants, trichloroethylene and characterized by higher sediment oxygen demand (SOD) and total organic matter (TOM) levels in proximity to the heavily industrialized port area near Apapa [4,58,64,67]. Studies on the microbial assemblages indicated that the bacterial communities around this area differ substantially from non-polluted sites in the lagoon [58] and revealed lower diversity and evenness in the microbial communities.…”
Section: Influence Of Pollutionmentioning
confidence: 91%